Real-time Petty Cash Monitoring: Inovasi Web untuk Pengelolaan Anggaran Operasional yang Efisien - Ridwan, Witsqa Inayatussholiha; Sarah, Ira Siti (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
The petty cash management at PT PLN (Persero) UP3 Garut was previously conducted manually using Excel files, which were then uploaded to the SAP ERP system for financial reporting. This process lacked real-time monitoring and automated alerts when expenditures approached budget limits. This study aims to develop a web-based application to digitally monitor petty cash through weekly transaction recording, nominal validation, automated notifications, and real-time reporting. The application was developed using the waterfall model through stages of requirement analysis, UML-based system design, implementation using PHP and MySQL, and black box testing. The main result of this study is a web-based petty cash monitoring system with key features such as login, transaction input, budget validation, budget recap, and automatic notifications. Testing results showed that all functions operated properly without errors and improved weekly recording efficiency by over 70%. Data is stored locally using XAMPP to ensure financial information security. The developed application meets the unit’s internal needs and contributes to better transparency and budget control. However, the system is not yet integrated with SAP, making automated integration a future development goal.